2017
DOI: 10.1055/s-0042-122780
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Frequencies of Peripheral Blood CD4+CD25+CD127–Foxp3+ in Patients with Graves’ Disease and Graves’ Orbitopathy: Enhancing Effect of Insulin Growth Factor-1 on Treg Cells

Abstract: Graves' orbitopathy (GO) is characterized by orbital T cell infiltration. We evaluated the regulatory T (Treg) cell fractions induced with IGF-1 in Graves' disease (GD) with and without GO. Peripheral blood mononuclear cells (PBMCs) were obtained from 13 patients with GD without eye manifestations; 10 patients with active GO; and 12 patients with nodular goiter (NG). All the patients from GD, GO, and NG were subclinical hyperthyroid. We analyzed the expression of Treg cell markers (CD4, CD25, CD127, Foxp3) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…Interestingly, IGF-1 promotes cell proliferation and lipid accumulation within orbital adipose tissue-derived stromal cells from patients with GO [11]. Recently we revealed that IGF-1 stimulation of peripheral blood mononuclear cells (PBMC) derived from GO patients resulted in significant increase of Treg frequency, thus demonstrating Treg-enhancing effects of IGF-1 [21]. This effect of IGF-1 may also impact Treg numbers locally within the orbital tissue from GO and therefore we compared the expression pattern of the IGF-1R with that of Foxp-3 in this current study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IGF-1 promotes cell proliferation and lipid accumulation within orbital adipose tissue-derived stromal cells from patients with GO [11]. Recently we revealed that IGF-1 stimulation of peripheral blood mononuclear cells (PBMC) derived from GO patients resulted in significant increase of Treg frequency, thus demonstrating Treg-enhancing effects of IGF-1 [21]. This effect of IGF-1 may also impact Treg numbers locally within the orbital tissue from GO and therefore we compared the expression pattern of the IGF-1R with that of Foxp-3 in this current study.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that Tregs play an important role in preventing autoimmunity and restraining responses of effector T cells, but the frequency and function of Tregs in the progression of AITD are discrepant [4, 25, 26]. Defective Tregs frequency has been widely reported to exist in Graves' disease [2732], while less evidence is available regarding Tregs in HT. In this regard, we assessed the classical CD4 + CD25 + Foxp3 + Tregs number and two key functional indicators in HT patients and HC.…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic mice over-expressing IGF-II, thymic cellularity was substantially increased and the frequency of normal T cells was increased, exhibiting a skew toward CD4 + lymphocytes (Kooijman, et al 1995b). IGF-I treatment of peripheral blood mononuclear cells from patients with GD could enhance the frequency of CD25 + Foxp3 + regulatory T cells (Pawlowski, et al 2017). IGF-I produced by bone marrow stromal cells stimulates the development of pro-B cells (Landreth, et al 1992).…”
Section: Igf-ir Was Proposed As a Ubiquitous Therapeutic Targetmentioning
confidence: 99%